What can ERPs tell us about the generation effect?. (29th September 2017) - Angel, Lucie; Fay, Séverine; Bouazzaoui, Badiâa; Taconnat, Laurence
Highlights: Memory performance was better with generated than read words. Encoding-related ERP activity was greater under the generate than the read condition. This additional activity was correlated with an executive control index. Abstract: The present experiment aimed to gain further understanding of the generation effect by investigating its neural correlates during encoding using event-related potentials (ERPs). Participants first encoded pairs of words under either a read or a generate condition and then completed a cued-recall task. Results confirmed the benefit of generation on memory performance. In addition, ERPs associated with the successfully encoded words had greater magnitude for generated than read words, from 900 to 1800 ms post-stimulus, on middle and bilateral frontal and parietal electrodes sites, mostly on the right hemisphere. Analyses also revealed that this greater activity was significantly correlated with executive control abilities but not with semantic knowledge. These findings show that generation is associated with greater later neural activity, suggesting the use of additional processes. Our findings also provide some evidence in support of the cognitive effort hypothesis of the generation effect.